2007
DOI: 10.1167/iovs.07-0024
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Inner Retinal Thickness in Patients with Autosomal Dominant Optic Atrophy Associated withOPA1Mutations

Abstract: PURPOSE.To determine the morphologic changes in the retina in the macula and around the optic disc in patients with autosomal dominant optic atrophy (ADOA) associated with a mutation in the OPA1 gene. METHODS. Cross-sectional images of the macular area of the retina were obtained by optical coherence tomography (OCT) in patients with ADOA who had a heterozygous mutation in the OPA1 gene. There were 15 eyes of eight patients from five families: four men and four women. The average age of the patients was 48.1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 40 publications
2
31
0
3
Order By: Relevance
“…10 On the other hand, the cause of RNFL loss in Alzheimer's and Parkinson's disease is multifactorial, including degeneration of RGC and through retrograde degeneration due to the loss of cortical neurons. 5,11,12 Pula et al 9 found a statistical significant decrease of mean macular thickness in five patients affected of SCA-3 compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…10 On the other hand, the cause of RNFL loss in Alzheimer's and Parkinson's disease is multifactorial, including degeneration of RGC and through retrograde degeneration due to the loss of cortical neurons. 5,11,12 Pula et al 9 found a statistical significant decrease of mean macular thickness in five patients affected of SCA-3 compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…The red Amsler grid is a particularly useful screening test. OCT is a useful ancillary test in the subacute and chronic stages by measuring the RNFL thickness and confirming thinning involving the PMB beginning in the inferotemporal sector (11)(12)(13)(14). In the later stages, OCT demonstrates thinning of RNFL thickness in all quadrants (9).…”
Section: Workup and Ancillary Testingmentioning
confidence: 99%
“…[7][8][9][10] These studies have shown that the thickness of specific retinal layers can help to diagnose and monitor pathologic changes in the macula resulting from retinal diseases, 11,12 glaucoma, 13 and optic neuropathy. 14 Several studies have used OCT to investigate relationships between variations in macular thickness and myopia. [15][16][17][18] The thicknesses of the retinal nerve fiber layer (NFL), ganglion cell layer (GCL), and inner plexiform layer (IPL) were reported by some authors to be thinner in myopic eyes compared to normal eyes.…”
mentioning
confidence: 99%